Efektivitas Teknik Permainan Kooperatif untuk Meningkatkan Keterampilan Sosial Siswa Sd Negeri 2 Curugbarang Pandeglang - Indry Setiawan Putri; Solih Solih; Alfiandy Warih Handoyo (CENDEKIAWAN, 2019)
Pre experimental design research with One Group Pre-Test-Post Test Design. The Research subject consisted of 8 student with low Social skills categories. Data collection methods used in The Research of using The questionnaire. The results showed the Average on a pre-test of 9,25 with percentage 28% while on With post-test of 22,375 with percentage 68% defined an increase in Social skill. Based on the pre-test and post-test results get an average gain of 13.12 with percentage of 40% which defines an effective cooperative game to improve social skills V grade students in public elementary school 2 Curugbarang, Pandeglang distric academic years of 2019/2020.